Behavioural and neuronal substrates of serious game-based computerised cognitive training in cognitive decline: randomised controlled trial - Esther Brill; Alexa Holfelder; Michael Falkner; Christine Krebs; Anna-Katharine Brem; Stefan Klöppel (BJPsych Open)
Background Investigations of computerised cognitive training (CCT) show heterogeneous results in slowing age-related cognitive decline.